Pelatihan Identifikasi Kerusakan dan Perbaikan Peralatan Rumah Tangga Berbasis Edukasi Dasar di Desa Janti Sidoarjo - Bambang Triono; Yayu Sriwahyuni Hamzah; Feby Salma Ayu Safitri (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2026)
Household appliances play an important role in supporting daily activities. However, the high rate of equipment damage and the limited technical knowledge among the community, especially housewives, often lead to dependence on repair services and increased household expenses. This community service program aimed to improve the ability of housewives to identify damage and perform simple repairs on household appliances independently. The program applied an educational and participatory approach through preparation, implementation, and evaluation stages. The implementation included the delivery of basic technical materials, demonstrations, hands-on practice, and interactive discussions. Data collection methods consisted of observations, questionnaires in the form of pre-tests and post-tests, interviews, and documentation, while data analysis employed both quantitative and qualitative descriptive approaches. The results showed a significant improvement in participants’ understanding, indicated by an increase in the percentage of correct answers from 15% to 80%. In addition, participants demonstrated better practical skills and greater confidence in carrying out simple repairs independently. This activity not only enhanced participants’ technical competence but also contributed to household cost efficiency and the reduction of electronic waste. Therefore, the program is considered effective in promoting community self-reliance and has the potential to be sustainably developed.